ADAPTABLE THRESHOLD ENERGY SCHEME FOR LOAD BALANCING TO IMPROVE NETWORK LONGEVITY IN WIRELESS SENSOR NETWORKS - Sumathi, R.; Srinivasan, R. (International Journal of Computing, 2010)
Energy efficiency is the major concern in the design of Wireless Sensor Network (WSN). It is imperative to develop protocols to distribute energy dissipation across nodes and reduces hotspots in the networks. In this paper, the Load Balancing Dynamic Adaptive Routing (LBDAR) a reactive and efficient data routing protocol is proposed for optimal distribution of load. Rather than finding an optimal path and use it for all communication, the proposed protocol dynamically constitutes energy sufficient routing path from source to sink for each round of communication, by considering two parameters, they are frequency count and adaptable threshold energy. The frequency count provides good chance for all the nodes to actively participate in forwarding data messages and the adaptable threshold energy prevents the early death of heavily involved nodes due to battery drain off, and thus helps in achieving our goal to distribute the load and hence enhances the network lifetime. The performance is evaluated by simulation using ns-2 simulator and results show that the LBDAR solves effectively the problem of load balancing and is also more efficient in terms of energy consumption and improves network lifetime.